Adverse Reaction Monitoring following Coronavirus Disease (COVID-19) Immunization among Health Care Workers of a Tertiary Care Hospital in India - Suraj B. Panchal; Latha Shivanand; Rakesh Navale; Somashekara S. Chikkannasetty; Amrutha D. Torvi; Rameez Ahmed; Satish Ghatage (Universitas Padjadjaran, Indonesia, 2022)
With the unprecedented and devastating impact of Corona Virus Disease (COVID-19) pandemic on public health, high coverage of safe and efficacious vaccines against COVID-19 disease could contribute to the control of the COVID-19 pandemic. However, in India vaccination strategy against COVID-19 was implemented to overcome this catastrophe as early as January 2021. Considering the novelty in adverse events and the dearth of research studies about the adverse event following immunization (AEFI) associated with COVID-19 vaccine, the present study aimed to determine the incidence and types of adverse events following COVID-19 vaccination among healthcare workers (HCWs). It was a prospective, observational study conducted among the HCWs of a tertiary care hospital who received the first dose of the ChAdOx1 nCoV-19 vaccine between January-March 2021. Systemic and local adverse events experienced up to the first 24 hours of vaccination were surveyed using Google Forms. Of the total 1045 HCWs who were vaccinated, 666 HCWs responded completely to the Google form. The majority (79.3%) of the participants were 18-30 years old. The most commonly reported AEFI were pain at the injection site (68.8%), fatigue (40.1%), myalgia (35.4), and malaise (35.0%). Among the systemic adverse events, the incidence of fatigue, and local adverse events, the pain at the injection site was considerably greater in the 18-30 years age group than in the other HCWs group (P < 0.001). The severity of most AEFI was mild-to-moderate in nature. Hence, this study concludes that AEFI associated with the ChAdOx1 nCoV-19 vaccine after a single dose was safe and tolerable. The maximum number of participants accepted AEFI because minor reactions would be common and treatable